Réponses

2013-04-15T19:59:37+02:00

(6t+4)(2+3t) = 12t +18t² + 8 + 12t

                       = 18t² + 12t + 12t + 8

                       = 18t² + 24t + 8

 

(m-3)² - (3m+4)(m+8) =  m² - 2 x m x 3 + 3² -(3m²+24m+4m+32)

                                        = m² -6m + 9 - ( 3m² + 28m+32)

                                        = m² - 6m + 9 - 3m² - 28m - 32

                                        = m² - 3m² - 6m - 28m + 9 - 32

                                        = -2m² - 34m -23

 

 

N'oublis pas de choisir la meilleure réponde, merci.